Visitantes florais de Erythrina speciosa Andr. (Leguminosae) - Vitali-Veiga, Maria J. [UNESP]; Machado, Vera L.L. [UNESP] (Sociedade Brasileira de Zoologia, 2000)
Inspite of Etythrina species exhibit morphologic attributes for adaptation to pollination by nectarivorous birds mentioned in the literature, E. speciosa is pollinated by lots of bees (Apinae and Meliponinae) which show a great urban occurrence. Systems of E. speciosa floral reproduction, fenology, diversity, frequency and constancy of insects visiting at different hours and flowering periods were studied. E. speciosa is Biocompatible, but xenogamy is the predominant system of reproduction. A large diversity of insects visiting the inflorescences was observed, with predominance of bees. The bee species showed a higher frequency: Apis mellifera Linnaeus, 1758 (45,0 %), Trigona spinipes (Fabricius, 1793) (28,6%), Trigona hyalinata (Lepeletier, 1836) (12,2 %) and the ant Zacryptoceruspusillus Klug, 1824 (2,8 %). Constant but not frequent were the bees (Apidae) Plebeia droryana (Friese, 1900), Friesella schrottkyi (Friese, 1900), Nannotrigona testaceicornis (Lepeletier, 1836), Tetragonisca angustula (Latreille, 1811), the wasps (Vespidae) Polybia paulista Ihering, 1896, Protopolybia exigua (de Saussure, 1854), Agelaia pallipes (Olivier. 1791), the ant (Formicidae) Pseudomyrmex sp. and the beetle (Chrysomelidae) Diabrotica speciosa (Germar, 1824). E. speciosa flowers were visited by hummingbirds (Trochilidae): Eupetomena macroura (Gmelin, 1788), Clorostilbon aureoventris (d'Orbigny & Lafresnaye, 1838) and Amazilia sp. The birds Passer domeslicus (Linnaeus, 1758) (Ploceidae) and Coereba flaveola (Linnaeus, 1758) (Emberizidac), also are present. The frequency and insect distribution were influenced by ambiental factors. Temperature, light, time, barometric pressure, relative humidity and wind velocity were significantly correlated with insect numbers. There is a visit sequence, by floral resource disponibility during the day, conditioned by transport ability, insect numbers and colony necessity, which begins by A. mellifera followed by meliponid bees. These bees make the pollination when they collect the pollen. There is a great animal variety which are sustained by flowers. It is suggested that E. speciosa is one important food source for urban fauna in winter, and so it should be utilized more frequently in streets, parks and gardens arborization.
Flowering visitors of Erythrina speciosa Andr., Leguminosae
Keywords: Pollination; Erythrina speciosa; bee; fenology; floral visitors